Oxidative Stress, Lipid Peroxidation, and Loss of Hyaluronic Acid in the Human Vitreous Affected by Synchysis Scintillans - Loredana Bergandi; Oleksii A Skorokhod; Rosalba La Grotta; Evelin Schwarzer; Raffaele Nuzzi (Journal of Ophthalmology)
The aim of this study was to assess the oxidative stress status in eyes affected by synchysis scintillans and to compare it to vitreoretinal disorders without synchysis scintillans. Human aqueous and vitreous humors were obtained during vitrectomy from thirty-seven otherwise healthy patients that were randomly chosen among patients that had to undergo a 25-gauge pars plana vitrectomy from the central vitreous cavity, for either synchysis scintillans (n = 16) or vitreoretinal disorders without synchysis scintillans (n = 21), such as idiopathic epimacular membrane (n = 12), macular hole (n = 5), or rhegmatogenous retinal detachment (n = 4). The redox parameters thiobarbituric acid reactive substances (TBARS), a measurement of lipid peroxidation, nitrite concentration, an estimate of nitric oxide (NO) production, 4-hydroxynonenal (4-HNE)-protein conjugates, a structural protein modification by lipid peroxidation product 4-HNE, and the antioxidative activities of Cu,Zn-superoxide dismutase (SOD), and catalase were measured in aqueous and vitreous humors and compared between synchysis scintillans affected and not-affected patients. TBARS and nitrite levels of the vitreous humor were significantly higher in patients with synchysis scintillans as compared to patients affected by vitreoretinal disorders without synchysis scintillans. Synchysis scintillans patients had significantly lower activities of SOD and catalase both in aqueous and vitreous humors than patients with vitreoretinal disorders without synchysis. The consequently higher lipoperoxide-dependent 4-HNE production in synchysis scintillans was detectable in aqueous and vitreous humors as a significant increased accumulation of 4-HNE-protein conjugates vs nonsynchysis vitreoretinal disorders. Additionally, hyaluronic acid (HA) was significantly decreased in the vitreous body of synchysis scintillans patients. The data consistently show that synchisis scintillans is accompanied by a redox imbalance with increased oxidative modifications of 4-HNE proteins and loss of HA, both of likely importance for remote damages of the retina. It remains to be proven whether a therapeutic strategy which targets oxidative stress may be effective in the treatment of synchysis patients.